Impact of United States political sanctions on international collaborations and research in Iran - Kokabisaghi, Fatemeh; Miller, Andrew C; Bashar, Farshid R; Salesi, Mahmood; Zarchi, Ali A K; Keramatfar, Abdalsamad; Pourhoseingholi, Mohammad A; Amini, Hosein; Vahedian-Azimi, Amir (My University, 2019)
International research collaborations improve individual, institutional and governmental capacities to respond to health crises and inequalities but may be greatly affected by political environments. Iran ranks highly in tertiary education, productivity growth, knowledge impact and successful patent applications. In many countries, economic hardship has correlated with increased international research collaborations. Some have hypothesised that financial constraint drives scholars to seek outside collaborations for cost and risk sharing, and to access funding, materials and patient populations otherwise unavailable. This paper explores the history and importance of US political sanctions on the health of Iran’s academic sector. Although Iran’s international research collaborations increased during periods of increased sanctions, the Pearson correlation coefficient between gross domestic product and international research collaborations was not significant (r=0.183, p=0.417). This indicates that other factors are at least in part responsible. Additionally, we found Iran’s quantitative (eg, publication number) and qualitative (eg, visibility indices) publishing metrics to be discordant (two-tailed Mann–Kendall trend; p<0.0002 for both). Reasons for this are multifactorial, including increased indexing of Iranian journals, willingness of lower visibility journals to handle manuscripts with Iranian authors, widespread linkage of career advancement to science visibility indices, and others. During periods of increased sanctions, Iranian scholars were increasingly denied opportunities to publish scientific findings, attend scientific meetings, access to essential medical and laboratory supplies and information resources. We conclude that academic boycotts violate researchers’ freedom and curtail progress. Free exchange of ideas irrespective of creed is needed to optimize global scientific progress.